The effect of armed conflict on saving rates: international evidence from 1980 to 2015 (2018)
The importance of savings rates on economic growth have been well studied among economic literature (Solow, 1956) finding that economies without higher levels of savings present problems when private investment is needed -- Current authors have found the determinants of savings and almost every author agree in variables as disposable income, education level and several other demographic variables (see Grigoli, Herman & Schmidt-Hebbel, 2018 and Doshi, 1994) -- In contrast, sociopolitical variables as measures for political instability and armed conflicts haven’t been included as determinants for savings although these factors should affect the life of individuals and at last their decisions -- According to several authors almost a half of the countries have suffered any kind of armed conflict or civil war in the 20th century (see Blattman & Miguel, 2010), so is feasible that these situations have certain effects over human behavior and their decision -- To test the hypothesis that armed conflicts have a determinant effect over human behavior and savings, a sample of 65 countries for the period between 1980 to 2015 is constructed and fixed effect of conflicts over the saving rates is tested including the traditional determinants of savings as control variables -- The results indicate that the probability of dying, explained in terms of life expectancy and death rate, have a negative effect over the saving rates, the results show that these results are worsened by the appearance of conflict